Activity-based funding based on diagnosis-related groups: The end of an era? A review of payment reforms in the inpatient sector in ten high-income countries - Ricarda Milstein; Jonas Schreyögg (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2022)
Background: Across the member countries of the Organisation for Economic Co-Operation and Development, policy makers are searching for new ways to pay hospitals for inpatient care. At present, the dominant payment system for inpatient services is activity-based funding based on diagnosis- related groups. Its focus on activity, however, does not support the transition from volume to value that most OECD countries are seeking to achieve. Methods: We reviewed reforms to payment systems in ten high-income countries (Australia, Austria, Canada (Ontario), Denmark, France, Germany, Norway, Poland, the United Kingdom (England), and the United States). Results: We identified four reform trends among the observed countries. First, they are reducing the overall share of inpatient payments based on DRGs. Second, they are implementing add-on payments for rural hospitals or excluding these hospitals from the DRG system entirely. Third, they are experimenting with episode-based payments, which use one joint price to pay providers for all services delivered along a patient pathway. Fourth, they are operating with financial incentives to shift the delivery of care to less costly setting. Some countries have combined some or all of these measures with financial adjustments for quality of care. Discussion: Countries are experimenting with new ways to pay hospitals for inpatient services. These reforms demonstrate a shift away from activity and efficiency towards a diversified set of targets, and mirror efforts being undertaken more broadly to slow the rise in health expenditures while improving quality of care. Very few of the reforms have been evaluated, and those that have are almost exclusively from the United States. Where available, the evidence points to mixed results. Conclusion: Countries are moving away from DRG systems. The degree to which they are reforming their payment systems within existing structures or are moving to alternative payment systems altogether reflects the underlying values of each health system. We strongly encourage countries to follow the example of the United States and to pilot and evaluate reforms in selected areas, and to make evaluations a mandatory part of payment reform initiatives.
Keywords: 330